The Friday Society - Kress, Adrienne (Dial Books, 2012)
Cora, Nellie, and Michiko, teenaged assistants to three powerful men in Edwardian London, meet by chance at a ball that ends with the discovery of a murdered man, leading the three to work together to solve this and related crimes without drawing undue attention to themselves.